Banned Black Cartoons - Ising, Rudolf; Jones, Chuck; Iwerks, Ub; Tashlin, Frank; Freleng, Friz (IHF, 2016)
"Little Black Sambo", a 1935 cartoon, includes four characters: Mammy, Sambo, a dog, and a tiger. The husband is conspicuously absent. The most intelligent character is the dog. Mammy speaks in racially stereotypical dialect, for example, she warns Sambo about the tiger: "That ol' tiger sho' do like dark meat!" The cartoon begins by playing on the stereotype of Blacks as physically dirty. Mammy scrubs the dirty boy in a washtub. When she finishes the water is as black as the ink-colored little boy. Mammy pats him with baby powder - black baby powder. When Sambo meets the tiger he is so scared his skin temporarily turns white. This idea is often seen in jokes about scared Blacks. Here is an example of one way that the fear and loathing of Blacks is negotiated: make the Black skin disappear. Bannerman's "Little Black Sambo" character was a clever little boy who outwitted several tigers; the Sambo character in this cartoon is a scared little "pickaninny" who runs, yelps, and dances, but never speaks. [www.ferris.edu]